Cover Picture: Effect of Cross‐Link Density on Carbon Dioxide Separation in Polydimethylsiloxane‐Norbornene Membranes (ChemSusChem 21/2015). Issue 21 (2nd November 2015) - Hong, Tao; Niu, Zhenbin; Hu, Xunxiang; Gmernicki, Kevin; Cheng, Shiwang; Fan, Fei; Johnson, J. Casey; Hong, Eunice; Mahurin, Shannon; Jiang, De‐en; Long, Brian; Mays, Jimmy; et al.
Abstract : The cover picture illustrates reduction of CO2 emission from a power plant by using a high‐performance passive polymer membrane. Designing new membranes with high permeability and efficient CO2 separation performance is imperative for treating the large volume of flue gas with minimum energy costs. This work reports the design, synthesis, and performance of newly developed lightly cross‐linked polydimethylsiloxane–norbornene membranes that show excellent CO2 permeability and CO2 /N2 selectivity. This finding can open up a new approach to enhance performance for gas separation and could elucidate additional factors important for the selective gas permeation mechanisms in rubbery polymers. More details can be found in the Full Paper by Hong et al. onpage 3595 in Issue 21, 2015 (DOI:10.1002/cssc.201500903 ).